Design of an Interdigital Structure Planar Bandpass Filter for UWB Frequency - S. M. A. Motakabber; M. N. Haidari (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A new topology of miniaturized interdigital structuremicrostrip planar bandpass filter for Ultra-Wideband (UWB) frequency has been discussed in this paper. The proposed design and its simulation have been carried out by using an electromagnetic simulation software named CST microwave studio. The Taconic TLX-8 microwave substrate has been used in this research. The experimental result and analysis have been performed by using the microwave vector network analyzer. The experimental result showed that the -10dB bandwidth of the filter is 7.5GHz. The lower and upper corner frequencies of the filter have been achieved at 3.1GHz and 10.6GHz respectively. At the center frequency of 6.85GHz, the -1dB insertion loss and the -7dB return losshave been observed. The simulated and experimental results are well agreed with a compact size filter of 19×21×0.5mm3.